Disrupted and Disconnected: Child Activities, Social Skills, and Race/Ethnicity During the Pandemic - Hernández, Racquel; Jabbari, Jason (Frontiers in Education, 2022)
Early in the COVID-19 pandemic, parents reported that their children spent the majority of their time at home, which can dramatically change their activities and negatively impact their social skills. However, research has yet to uncover the relationships between changes in activities during the pandemic and children’s social skills, nor the degree to which these relationships might differ across race and ethnicity. To fill this gap in knowledge, we leverage a nationally representative survey with 948 parents conducted in May 2021 and use Likert scaled questions to explore the relationships between increases or decreases across a range of child activities (e.g. outdoor activities, school activities, friend activities, extracurricular activities, and screen activities) and better or worse child social skills during COVID-19. By exploring the relationship between changes in children’s activities and changes in children’s social skills during the first 15 months of the pandemic, we provide new evidence for the long-term effects of COVID-19’s disruptions on children’s social development, while highlighting opportunities to improve children’s social skills through targeted activities. First, we used a multivariate linear regression strategy to capture associations between changes in child activities and changes in child social skills, while accounting for a robust set of student, school, and parent covariates. Then, we used interaction terms to examine the moderating role of race and ethnicity on the associations between changes in child activities and changes in child social skills. We found that an increase in outdoor activities, school activities, friend activities, and extracurricular activities were significantly associated with an increase in social skills. We also found evidence that for Hispanic households an increase in school activities was especially important for the development of social skills, and that for Black and Hispanic households, an increase in screen time was associated with an increase in social skills.